Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages Events at the meetings in January and February, 1946, of the United Nations General Assembly and Security Council in London showed that the breach between Russia and the Western Powers was widening. Bevin regarded Russia's action in the Azerbaijan province of Persia as aggressive. Quickly, British intervention in Greece and Indonesia was dragged into the limelight by Russia and her satellites. In truth, the attitude of the Labour Government was identical with that of the more intelligent senior officers of the armed services and of the Foreign and Colonial Offices. No wonder Attlee and Bevin resisted any suggestions from their own Left Wing, that the personnel of Ambassadorial and Colonial Governor rank should be changed. It would bring in the spoils system, and undermine efficiency, they said. It is as well, in order to show what these high British officials really are like, to refer to Wendell Willkie's account given in his 1943 book, "One World." This successful, modern-minded American businessman records: "At Alexandria, Admiral Harwood invited to dine with us ten of his compatriots in the naval, diplomatic or consular service ... I tried to draw out these men, all of them experienced and able administrators of the British Empire, what they saw in the future, and especially in the future of the colonial system and of our joint relations with the many peoples of the East ... These men, executing the policies made in London, had no idea that the world was changing. The British colonial system was not perfect in their eyes ; it seemed to me simply that no-one of them had ever thought of it as anything that might possibly be changed or modified in any way. The Atlantic Charter most of them had read about. That it might affect their careers or their thinking, had never occurred to any of them." (pp. 14-15). It is with human instruments like these that Labour's foreign policy is fashioned and then carried out. The Labour Government acted as their officials wanted when Attlee refused to implement the Anglo-American Palestine Commission's suggestion that 100,000 European Jews be admitted, unless U.S.A. was prepared to help. This at a time when delay and hesitation would make the Palestine situation rapidly worse. On India, the Cabinet was slow to move. It seems to have been the mutinies in the Indian Navy and Air Force, early in 1946, that finally convinced officials and Ministers that something big had to be done. 8 15X/2/98/21